Emerging economies of East and South East Asia : some salient points about technology's role in economic development / Elias Sanidas - Sanidas, Elias (Faculty of Business and Management, 2014)
This area of East and South East Asia is characterized by the following traits: very large population; tendency and ability for detail; imitation rather than creation; ability for organization; tendency for corruption; tendency for autocratic regimes; in the process of an industrial revolution; technological imitation; nationalism without boundaries; wide range of GDP per capita and poverty; litter and pollution problems without solutions; natural disasters; exports oriented; high urban development; Chinese culture influence; FTAs (Free trade agreements) and ASEAN; FDI rather high; disparities between East Asia and other Asian areas; production networks through Japan‟s and South Korea‟s roles in international division of labor.